Activity, distribution and regulation of phosphofructokinase in salivary gland of rats with streptozotocin-induced diabetes Atividade, distribuição e regulação da fosfofrutoquinase em glândulas salivares de ratos com diabetes induzido por estreptozotocina - José Nicolau; Douglas Nesadal Souza; Fernando Neves Nogueira (Sociedade Brasileira de Pesquisa Odontológica, 2006)
Although the influence of diabetes on salivary glands is well studied, it still presents conflicting results. In this work, the regulation of the phosphofructokinase-1 enzyme (PFK-1) was studied utilizing the salivary glands of rats. Diabetes was induced by a single intraperitoneal injection of streptozotocin (60 mg/Kg of body weight) in rats (180-200 g). The animals were killed 30 days after the induction of diabetes and the submandibular and parotid salivary glands were used. Hyperglycemia was evaluated by blood sugar determination. The distribution of PFK-1 between the soluble and cytoskeleton fractions, the phosphate content of PFK-1, the content of fructose-2,6-bisphosphate and the activity of the PFK-2 enzyme were determined. The calculated relative glandular weight showed a higher value for the parotid gland in comparison with the control, but not for the submandibular gland. The activity of PFK-1 expressed per gland showed no variation between diabetic and control animals. However, considering the specific activity, the soluble enzyme presented a value 50% higher than that of the control and the cytoskeleton bound form increased by 84% compared to the control. For the parotid gland, no difference in the specific activity between diabetic and control animals was observed. On the other hand, the activity per gland of the soluble enzyme increased in the diabetic animals. The phosphate content of PFK-1 increased in the submandibular and parotid glands of diabetic rats. Both the content of fructose-2,6-bisphosphate and the active form of PFK-2 were reduced in the diabetic glands. In conclusion, the increase in the activity of PFK-1 observed in the salivary glands of rats with streptozotocin-induced diabetes does not seem to be due to its modulator fructose-2,6-bisphosphate. Apesar de existirem muitos estudos sobre a influência do diabetes nas glândulas salivares, esses apresentam resultados conflitantes. Neste estudo, a regulação da enzima fosfofrutoquinase-1 (PFK-1) foi estudada utilizando-se glândulas salivares de ratos. O diabetes foi induzido por uma única injeção intraperitonial de estreptozotocina (60 mg/kg peso corporal) em ratos (180-200 g). Os animais foram sacrificados 30 dias após a indução do diabetes e utilizaram-se as glândulas submandibular e parótida. A hiperglicemia foi avaliada por determinação da glicemia sanguínea. A distribuição da PFK-1 entre frações solúvel e ligada, concentração de fosfato na PFK-1, concentração de frutose-2,6-bisfosfato e a atividade da enzima PFK-2 foram determinadas. O cálculo do peso glandular relativo mostrou um aumento na glândula parótida de ratos diabéticos comparados ao controle, o que não ocorreu na glândula submandibular. A atividade da PFK-1 expressa por glândula não mostrou variação entre animais diabético e controle. Contudo, considerando a atividade específica, a fração solúvel da enzima mostrou aumento de 50% com relação ao controle e a fração ligada ao citoesqueleto um aumento de 84% com relação ao controle. Na glândula parótida não foi observada diferença na atividade específica entre os grupos diabético e controle. Por outro lado, a atividade por glândula da fração solúvel aumentou nos animais diabéticos. A concentração de fosfato da PFK-1 aumentou nas glândulas submandibular e parótida nos animais diabéticos. Tanto a concentração de frutose-2,6-bisfosfato quanto a forma ativa da PFK-2 mostraram redução nas glândulas salivares. Concluindo, o aumento na atividade da PFK-1 observado nas glândulas salivares de ratos com diabetes induzida por estreptozotocina não parece ser modulado pela frutose-2,6-bisfosfato.